Pembelajaran Berdasarkan Masalah dengan Pendekatan Deduktif-Induktif pada Matakuliah Persamaan Differensial Biasa - Ahmad Talib (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2022)
This research applies problem based learning with deductive-inductive approach to the course of ordinary differential equation (PDB). This study aims to apply problem-based learning steps involving the student's deductive-inductive thinking approach, applying the teaching materials of PDB involving the student's deductive-inductive thinking approach, but it is also expected that these teaching materials can maximize the deductive-inductive thinking approach, and help students improve their way of thinking, based on the material characteristics of PDB.The research method used is classroom action research, to maximize the deductive-inductive thinking ability of the students. As the paradigm of class action research, the implementation of this research includes planning activities, actions, observation and cyclic reflection, the implementation is divided into two cycles, the first cycle is for two months or seven meetings, and the second cycle is also for two months or seven meetings in the Semester Academic Year 2016/2017, which amounted to 30 students, at Mathematics Department FMIPA UNM Makassar.The results of the first cycle of this study show that problem-based learning with deductive-inductive approaches helps a lot of students, even though at first the students still seem unwilling to apply how their mindset in learning and solving problems. After being given some strengthening, in the following weeks the interaction of learning progressed significantly. Learning scenarios and teaching materials as guidelines for the implementation of lecturing activities, in line with the tendency of the student's deductive-inductive thinking approach. In the second cycle, it shows that the students have been able to handle the problems themselves in applying the inductive-deductive approach, both in terms of improvements of the mindset, the way of starting it and the logic used in working on the problems. Key words: Problem based learning, Deductive-inductive approach, PDB